A critique of monetary policy : theory and British experience - Dow, J. C. R. (J. Christopher R.) (Clarendon Press ; Oxford University Press, 1988)
In this book, the authors expound a theory of monetary policy, and examine how it has worked in the UK. They analyse the behaviour of the banking system and the difficulties of central bank control. In a clearly written account they explain the changes taking place in monetary policy.